Analisis Perbandingan Metode Pemberian Kredit Pada Bank Konvensional Dengan Pembiayaan Murabahah Pada Bank Syariah. (Studi Pada PT. Bank Mandiri Tbk. Dan PT. Bank Syariah Mandiri) - Amangku Depri M Bustaman; Ridwan Ibrahim (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2015)
Credit is loaning money or bills that can be equated with it based on agreements between banks and other parties. Murabaha is a sale and purchase agreement where the seller stated the cost and profit margin agreed between the seller and buyer.The data collecting methods uses primary data and secondary data, while the method of analysis used is descriptive qualitative method. The results showed that there are similarities in Bank Mandiri’s lending procedures and Bank Syariah Mandiri’s murabaha financing.But also there is a difference between the lending by bank Mandiri and Bank Syariah Mandiri’s Murabaha Financing, that is the calculation method of credit funds and financing needs. The method used by Bank Mandiri is the Working Capital Turnover Method, While Bank Syariah Mandiri uses the cash flow projection analysis method. There is also a fundamental difference of credit with murabaha in how the profit is earned. Bank Mandiri makes profit derived from the interest, while the BankSyariah Mandiri profits derived from murabaha financing obtained from an agreed margin.